Pemberdayaan Perempuan Upaya Pencegahan penyakit Degeneratif Keluarga - Januarti, Luluk; soliha, soliha; Yulianto, Sofi (ABDIMASNU: Jurnal Pengabdian kepada Masyarakat, 2024)
Women's empowerment is an activity that involves women to increase awareness, willingness, and ability for every woman to live a healthy life so that the highest degree of public health can be realized. The incidence of degenerative diseases is increasing. One of the problems that occur is the ignorance of sufferers about their health conditions. The lack of understanding and self-awareness of women to carry out routine examinations so that degenerative diseases develop and some of them develop into palliative diseases, it is necessary to strive for public health management training activities related to degenerative diseases. With the method of empowering women, counseling, and public health maintenance can be started from the awareness of every individual, family, group, and the wider community. The purpose of this service is to provide knowledge education to the community through women about the importance of knowing about degenerative diseases and providing knowledge about degenerative diseases and prevention that must be known related to reducing the risk of degenerative disease. Through this service program, women's knowledge can raise awareness and motivate women to be willing and able to monitor and solve health problems that occur in them independently and consistently, awareness from women to always maintain a good lifestyle to prevent the occurrence of degenerative diseases and the formation of cadres to evaluate women to always maintain their health.